Differentiated instruction in primary mathematics: Effects of teacher professional development on student achievement. (April 2018) - Prast, Emilie J.; Van de Weijer-Bergsma, Eva; Kroesbergen, Evelyn H.; Van Luit, Johannes E.H.
Abstract: This large-scale study examined the effects of a teacher professional development (PD) programme about differentiated instruction on students' mathematics achievement. Thirty primary schools (N = 5658 students of grade 1–6) divided over three cohorts participated: Cohort 1 received the PD programme in Year 1, Cohort 2 in Year 2, and Cohort 3 was control. During the PD, teachers learned how to adapt mathematics education to diverse educational needs using within-class ability groups. In Year 1, the PD had a significant small positive effect on student achievement growth. The effect size was similar for low-achieving, average-achieving and high-achieving students. In Year 2, no significant effects were demonstrated. In sum, teacher PD about differentiation has the potential to promote the achievement of all students. However, implementing differentiation is not straightforward and future research is necessary to unravel which factors make PD about differentiation succeed. Highlights: Teacher professional development about differentiation raised student achievement. Teachers learned how to adapt mathematics education to diverse educational needs. Students of participating teachers showed more achievement growth. Effects were similar for students of diverse achievement levels.